Earnings Management dan Beban Pajak - Juliati Juliati; Ahmad Ridwan; Sofyan Hadinata (Jurnal Akuntansi dan Bisnis, 2014)
This study have a goal to give empirical evidence that deferred tax expensea and current tax expense have an aility to detect eanings management at changing of tax rate like the study that be done(Philips, 2003; Dhaliwal, 2003, Yulianti, 2005 dan Hendrawan, 2007). This study used discretionary accruals to measure earnings management. Data used manufacturer company that list at Indonesian Stock Exchange 2008 -2012. The test of liner regression showed that deferred tax expense and current tax expense have an ability to detect earnings management.